Enseñanza de los problemas de contaminación a través de la plataforma Classcraft para estudiantes de Educación Media de la I.E.D. Almirante Padilla de USME (2022)
Education is fundamental for society with the lest to generate effective solutions to pollution problems. This paper is elaborated from this need and taking into account the difficulties evidenced in the I.E.D. Almirante Padilla located in Usme locality in environmental education, for this reason is elaborated a digital teaching material, supported by the Classcraft gamified platform with the objective to bring near to students to pollution problems in their influence area and starting to this they can develop skills in preparation and implementation of environmental projects aligned to the PRAE of the institution. This resource generates great acceptance by students in the implementation process, they perceive that it is attractive, with an easy and interactive sequence. By evaluators, the relevance of the material and the innovation that involves the students with the reflection of the pollution problem are highlighted.